The Role of Bhabinkamtibmas in Preventing Criminal Acts of Theft of Two-Wheeled Motorized Vehicles - Singajuru, Furqon Saibatin (Police Studies Review, 2024)
This research is motivated by the increase in cases of two-wheeled carburetor caused by dense and full parking lots in Coblong District. The repressive efforts that have been carried out do not produce a sense of deterrence towards the perpetrators so a preventive effort is put forward. For this reason, a study was conducted aimed at describing the role of Bhabinkamtibmas which was carried out by the Cobbin Police Unit Unit and the influencing factors. This research was conducted with a qualitative approach, using descriptive research methods. The location of the study was carried out in the jurisdiction of the Coblong Police Station. The data sources used in this study are primary, secondary and tertiary data sources. The technique used by the writer is using interview, observation, and document study techniques. To determine the validity of the data the author uses triangulation techniques. The technique used by the author in analyzing data using data reduction, data presentation, and drawing conclusions. Based on the results of the study, the implementation of counseling carried out by the Cobab Police Department Bhabinkamtibmas has been carried out well, but the cases of fraud in the District of Coblong are still increasing, because the counseling carried out has not been focused on a particular problem and is less efficient. In addition, there are many factors that hamper the role of Bhabinkamtibmas in conducting counseling such as human resources, budget, facilities and infrastructure. In conclusion, counseling conducted by Bhabinkamtibmas has not been fully effective. Prevention efforts carried out are still not focused on a problem, the focus of counseling is too broad resulting in difficult to understand by the community and especially students. The obstacles in counseling are also felt by Bhabinkamtibmas because it is difficult to arrange the time to carry out counseling to students. Therefore, it is necessary to have a division of tasks in accordance with the prevailing work procedures and centralized counseling.